2020
DOI: 10.3390/biom10020334
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Infectives Restore ORKAMBI® Rescue of F508del-CFTR Function in Human Bronchial Epithelial Cells Infected with Clinical Strains of P. aeruginosa

Abstract: Chronic infection and inflammation are the primary causes of declining lung function in Cystic Fibrosis (CF) patients. ORKAMBI® (Lumacaftor-Ivacaftor) is an approved combination therapy for Cystic Fibrosis (CF) patients bearing the most common mutation, F508del, in the cystic fibrosis conductance regulator (CFTR) protein. It has been previously shown that ORKAMBI®-mediated rescue of CFTR is reduced by a pre-existing Pseudomonas aeruginosa infection. Here, we show that the infection of F508del-CFTR human bronch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 42 publications
0
29
0
1
Order By: Relevance
“…Then, CFTR inhibitor (CFTRinh-172, 10 µM) was added to deactivate CFTR. The peak changes in fluorescence to CFTR agonists were normalized relative to fluorescence immediately before agonist (forskolin) addition [ 24 , 28 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Then, CFTR inhibitor (CFTRinh-172, 10 µM) was added to deactivate CFTR. The peak changes in fluorescence to CFTR agonists were normalized relative to fluorescence immediately before agonist (forskolin) addition [ 24 , 28 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Immunoblotting: WT and KO-CFTR 16HBE14o-cells were grown as previously described. [70] Following 7 d of culture on Jag1-HA versus HA hydrogels, the cells were lysed in a modified radioimmunoprecipitation assay (RIPA) buffer (50 × 10 −3 m Tris-HCl, 150 × 10 −3 m NaCl, 1 × 10 −3 m EDTA, pH 7.4, 0.2% SDS, and 0.1% triton X-100) containing a protease inhibitor cocktail (Roche, Mannheim, Germany) for 10 min. [71] Soluble fractions were analyzed by SDS-PAGE on 6% tris-glycine gels (Life Technologies).…”
Section: (13 Of 15)mentioning
confidence: 99%
“…We can imagine that the improvement of various dysregulated parameters will have long-term effects on the inflammation present in CF patients, even if indirectly. A recent article has highlighted that by Tobramycin or the AMP, 6K-F17 could restore the effects of Orkambi on p.Phe508del-CFTR protein, suggesting a significant role of infection in the CF pathology ( Laselva et al., 2020 ). Furthermore, using this approach, they have demonstrated that the active AMP can down-regulate the expression of pro-inflammatory cytokines like IL-8, IL-6, and TNF-α in p.Phe508del-CFTR human BECs ( Laselva et al., 2020 ).…”
Section: Novel Anti-inflammatory Approachesmentioning
confidence: 99%